Network-on-Chip Paradigm for System-on-Chip Communication - Rahmat Budiarto; Lelyzar Siregar; Deris Stiawan (Computer Engineering and Applications Journal, 2017)
Developments of modern technologies in electronics, such as communication, Internet, pervasive and ubiquitous computing and ambient intelligence have figured largely our life. In our day micro-electronic products inspire the ways of learning, communication and entertainment. These products such as laptop computer, mobile phones, and personal handheld sets are becoming faster, lighter in weight, smaller in size, larger in capacity, lower in power consumptions, cheaper and functionally enhanced. This trend will persistently continue. Following this trend, we could integrate more and more complex applications and even systems onto a single chip. The System-on-Chip (SoC) technologies, where complex applications are integrated onto single ULSI chips became key driving force for the developments.